ADVANTAGES OF RICE PLANTED BY THE ACHAT METHOD (British Journal of Global Ecology and Sustainable Development, 2024)
Crop rotation of wheat and early-ripening rice in the same field has given good results. If rice seeds are sown in open fields from early spring, a lot of water is used. Therefore, one of the effective ways to save water is to grow rice by seedling method.